3 2 + 5 + 3 2 − 5 = ?
Give your answer to 3 decimal places
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
★【Nice coloring】★
nice solution .. +1
Bro cong!!!!and ru solution and my solution is same but you know(-1)^(1÷3) is complex so who u write this -1tell me.....and no answer then ur solution were wrong..
Log in to reply
Ask yourself what value should be multiplied 3 times to get a real one.
3
−
1
×
−
1
×
−
1
=
−
1
. However, there are three values where one is real and two are complex.
As you know
ι
=
−
1
=
(
−
1
)
2
1
.
( − 1 ) 3 1 = ( − 1 ) 2 1 × 3 2 = ι 3 2 ≈ 0 . 5 0 0 + 0 . 8 6 ι
I did it the same way as Abhay....but how can you say that (-1)^(1/3) is complex.? In cube roots none of the values can be complex.!
I have an algebraic-number-theoretic solution to this question. Let x = 3 2 + 5 + 3 2 − 5 . Thus, we have
x − 3 2 + 5 − 3 2 − 5 = 0
We have for numbers a , b and c such that a + b + c = 0 , then a 3 + b 3 + c 3 = 3 a b c . (This is not too hard to show and is left as an exercise for the reader.) Thus, we have
x 3 − ( 2 + 5 ) − ( 2 − 5 ) x 3 − 4 x 3 + 3 x − 4 ( x − 1 ) ( x 2 + x + 4 ) = 3 x 3 ( 2 + 5 ) ( 2 − 5 ) = 3 x 3 − 1 = 0 = 0
Note that x 2 + x + 4 has no real solutions, and we are assumed to take only the real cube root. Thus, the value must be 1. Therefore, 3 2 + 5 + 3 2 − 5 = 1 .
Interesting approach used here.
I'm not sure to what extent it is "number-theoretic". Seems mostly algebraic to me.
¶Superb¶ (+1)
I have also used the same identity.
Nicely done. +1 !
Same approach! A quite standard approach for finding values of this form.
3 2 + 5 = 2 1 + 5
3 2 − 5 = 2 1 − 5
3 2 + 5 + 3 2 − 5 = 2 1 − 5 + 2 1 + 5 = 1
@Sam Bealing 3 2 + 5 = ϕ ,the golden ratio ,that's cool!Can you show how?
Log in to reply
⇒ 3 2 + 5 = 3 8 8 ( 2 + 5 ) = 3 8 1 6 + 8 5 = 3 8 1 5 + 1 + 5 5 + 3 5 = 3 ( 2 1 + 5 ) 3 = 2 1 + 5 = ϕ
Log in to reply
Great job!That's correct :)
Log in to reply
@Rishabh Tiwari – Oh...Sorry fixed.
Problem Loading...
Note Loading...
Set Loading...
Let A = 3 2 + 5 , B = 3 2 − 5 .
And, ⇒ S = A + B = 3 2 + 5 + 3 2 − 5
Now, Cubing both sides.
⇒ S 3 = ( A + B ) 3
= A 3 + B 3 + 3 A B ( A + B )
= A 3 + B 3 + 3 A B S ...... ( ♧ ) [ Since , ( A + B ) = S ]
Thus,
⇒ A 3 + B 3 = ( 3 2 + 5 ) 3 + ( 3 2 − 5 ) 3
= 2 + 5 + 2 − 5
= 4
⇒ 3 A B = 3 ( 3 2 + 5 ) ( 3 2 − 5 )
= 3 ( 3 4 − 5 )
= 3 ( 3 − 1 )
= 3 × ( − 1 )
= − 3
Now, putting ( A 3 + B 3 ) = 4 and ( 3 A B ) = − 3 in ( ♧ ) .
⇒ S 3 = 4 − 3 S
S 3 + 3 S − 4 = 0
( S − 1 ) ( S 2 + S + 4 ) = 0
S − 1 = 0
S = 1
⇒ 3 2 + 5 + 3 2 − 5 = 1 .
Note : There is a possibilty that ( S 2 + S + 4 = 0 ) ,but this is not possible because its roots are non-real complex numbers.And the surds given is real.